THE COMMON GRAMMATICAL ERRORS IN WRITING NARRATIVE ESSAY OF STUDENTS AT THE YOUTH RESOURCE CENTER, SAVANNAKHET - Phommavongsa, Khamlan; Xaysetha, Soulideth; Phomchaleun, Somxay (Universitas Muhammadiyah Surakarta, 2021)
The research aimed to investigate types of common grammatical errors and dominant errors in writing narrative essays of students at the Youth Resource Center, Savannakhet. This study focuses on English students at the Youth Resource Center Savannakhet. The study employed a qualitative method. A sample group was 19 (12 male and 7 female) English students who learn English as an extra class. Data collection was conducted by testing writing narrative essay. The students were requested to write descript based on their stories under the theme: unforgettable moments in life. It’s consisting their experiences, holidays, and else. The researcher was analyzed data by using a descriptive initially statistic, a complete program Excel to present the data. As the result revealed that: there were 6 categories of common grammatical errors in students’ narrative essay writing such verb-tense there were 120 times with 28%, punctuation which came 99 times with 24%, spelling happened 63 times equal 15%, preposition came with 59 times with 14%, capital letter happened 58 times with 14%, and last was article error occurred 21 times with 5%. The most dominant type of grammatical error is verb-tense came with frequency 79. This was because of the students’ lack of knowledge in grammatical writing skill.